A study of processes in the activities headings from an english coursebook: a systemic-functional perspective of teaching and learning practices - Costa, Patrícia Helena da Silva (2017)
This study investigates the adequacy of the english coursebook used in an acceleration program from SME-RJ, the Acelera Brasil Program, which is sociointeracional in nature. Taking Systemic-Functional Linguistics as its socio-semiotics language theory and using specifically the Transitivity System, the study analyzes the processes in the activities headings, seeking to understand the nature of teaching and learning practices which constitute the book. The results point to pedagogical conceptions dissociated from critical issues and discussion of ideological bias, leading to discrepancies between the Program and the coursebook.